Western Existentialism in Selected Translated Malay Absurd Plays from an Islamic Perspective - Ahmad, Mas Rynna Wati (2011)
This study focuses on the adaptations of the absurd techniques applied by the three playwrights, Dinsman, Mana Sikana and Anuar Nor Arai during the period of Experimental Theatre. The research aims to give a new sphere of study in the area of theatrical arts, that not many intend to see further than the appropriation of absurd theatre in highlighting the most fundamental problems significant to the philosophical perspectives. The thesis focuses on the techniques used that are applicable to the theatre in Malaysia, especially in relation to the local social changes and political scenarios. The methodology of this research is carried out by focusing on the translated drama texts and interview data of the three playwrights. It is argued that these three playwrights are inclined to use the Western framework of the Theatre of the Absurd. For this study, Jean Paul Sartre’s The Existentialism and Human Emotions and Albert Camus’s Concept on Meaninglessness are adopted here to examine the western absurd theatre technique and its influence. It is found that Dinsman, Mana Sikana and Anuar Nor Arai have evidently adapted their own version of absurd plays. Nevertheless their works reflect a deeper discussion on existential issues through the perspective of Islam, hence an Islamic perspectives on the subject of existentialism is called for to analyze the texts. For this purpose, Al-Ghazali’s The Alchemy of Happiness and Al-Attas’s Concepts of Happiness in Islamic Metaphysics will able to highlight the findings of this study. Though these absurd dramatists have been heavily criticized for their experimentations, their works reflect authentic personal predicaments in finding the meaning of existence especially in a society that ignores the self in its efforts at social cohesion and religious discipline. This research also has found that these playwrights’ highlight their search for solutions for the personal meanderings as a result of modernization. Their solution incorporates the idea of persuading the society to return to their roots and adhered to the teachings of Islam in a fulfillment of a blessed life. Thus their works adhered to what is termed by theatre scholars as Theatre of the Absurd ‘ala’ Malaysia.